Maternal obesity and risk of adverse obstetric outcomes in Malaysia - Loh, Huai Heng; Haslinda, Taipin; Asri, Said (Annals, Academy of Medicine, Singapore, 2021)
Obesity during pregnancy is associated with increased risk of adverse health outcomes such as gestational diabetes mellitus (GDM), hypertension and preeclampsia.1 Unlike the well-known association between maternal hyperglycaemia and pregnancy outcomes, the effect of obesity in pregnancy has drawn some controversial conclusions.1 Data are even scarcer in Southeast Asia countries. In this research, we examined prospectively the effect of obesity in pregnancy and gestational weight gain (GWG) on pregnancy outcomes.